Cervical chondrocutaneous branchial remnant: A rare second branchial arch anomaly - T.A. Holtestaul; S.L. Rooney; M.A. Escobar (Elsevier, 2021)
Cervical chondrocutaneous branchial remnants are rare second branchial arch remnants which present in children as small, slow-growing nodules in the lower third of the neck anterior to the sternocleidomastoid muscle. They are most commonly unilateral and do not penetrate deeper than the SCM fascia. They are treated with complete surgical excision for cosmesis and pathologic diagnosis. We present a case of a right-sided CCBR in a three-year-old male treated with complete surgical excision.